Evaluation of exome sequencing data & mutation screening in GDAP1, GJB1, MPZ, NDRG1 and PMP22 genes in Turkish CMT patients - Sıvacı, Merve. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Charcot-Marie-Tooth (CMT) disease which is an inherited peripheral neuropathy is an excellent candidate to be analyzed by exome sequencing because of its locus heterogeneity and low prevalence. Protein-coding regions, ‘the exome’, constitute only 1% of the human genome, but 85% of the functional variations are found within these regions. Recent developments in sequencing techniques have made exome sequencing an alternative approach for disease-causing variation identification with its cost-effective feature when compared with whole genome sequencing. In the first part of this study, seventeen Turkish CMT patients were exome sequenced and the data obtained from sequencing was evaluated. Two novel variations in MFN2 gene as well as a novel splicing variant in GJB1 were confirmed in three families. In addition, in the other patients, novel variations in DNM2, LRSAM, FGD4 and KIF1B genes were identified, but they should be validated in other family members and also in controls. Previously identified mutations in AARS and DNM2 genes were found to be causative in two other families. Besides, possible novel genes were identified but needs confirmation in other patients. The data also revealed seven variations in CMT genes observed in all seventeen patients. Six of them have been previously reported as SNPs and one was novel probably representing a common variation in our population. In the second part of the study, eight other Turkish CMT patients were screened for mutations in the genes, GDAP1, GJB1, MPZ, NDRG1 and PMP22. A novel variation in PMP22 was identified for one patient and three previously reported SNPs were detected in GDAP1 for another patient. The presence of the founder p.R148X mutation in NDRG1 was also confirmed in two affected brothers. These data show the importance of clinical use of whole exome sequencing technology in CMT patients and other genetically heterogenous diseases as it allows the identification of disease-causing variants in a shorter period of time, compared to mutation screening in known CMT genes.
Keywords: Charcot-Marie-Tooth disease -- Turkey.; Mutation (Biology); Linkage (Genetics)